Accreditation in continuing veterinary education: development of an accreditation system and selection of accreditation criteria - Kareskoski, Maria (Frontiers in Veterinary Science, 2023)
With the increased supply and demand of veterinary continuing education (CE) and the growing number of CE providers, a clear need has arisen for a multinational accreditation system for veterinary CE. The objective of this document is to describe the current state of veterinary CE accreditation and the development of an accreditation system for veterinary CE, and discuss accreditation criteria and their pedagogical and practical significance. The hypothesis is that a profile of essential, pedagogically grounded, accreditation criteria can be established and utilized effectively in quality assessment. Accreditation criteria for veterinary CE can be created based on four selection principles: educational minimum requirements, coherence, efficacy, and assessability. The selected educational quality criteria are related to needs assessment, correlation of target audience and level of instruction, definition of scope, workload, and number of credits, organizer and instructor qualifications, constructive alignment, assessment of learning, learner engagement, and scientific quality of CE content. The created accreditation criteria and protocols should be regularly reevaluated and modified in close collaboration with the relevant stakeholders. The desired outcome of CE, including behavior change and improvement of practice and ultimately human and animal health, remains challenging to predict based on course descriptions by the providers, and further research is needed.